Highly Sensitive Electrochemical Determination of Butylated Hydroxyanisole in Food Samples Using Electrochemical-Pretreated Three-Dimensional Graphene Electrode Modified with Silica Nanochannel Film - Chengqing Huang; Shiyue Zhang; Xinying Ma; Fei Yan; Weizhong Tang (Nanomaterials, 2024)
The sensitive detection of antioxidants in food is essential for the rational control of their usage and reducing potential health risks. A simple three-dimensional (3D) electrode integrated with an anti-fouling/anti-interference layer possesses great potential for the direct and sensitive electrochemical detection of antioxidants in food samples. In this work, a 3D electrochemical sensor was developed by integrating a 3D graphene electrode (3DG) with vertically ordered mesoporous silica film (VMSF), enabling highly sensitive detection of the common antioxidant, butylated hydroxyanisole (BHA), in food samples. A simple electrochemical polarization was employed to pre-activate the 3DG electrode (p3DG), enhancing its hydrophilicity. Using the p3DG as the supporting electrode, stable modification of VMSF was achieved using the electrochemical assisted self-assembly (EASA) method, without the need for any adhesive agents (VMSF/p3DG). Taking BHA in food as a model analyte, the VMSF/p3DG sensor demonstrated high sensitivity, due to the enrichment by nanochannels, towards BHA. Electrochemical detection of BHA was achieved with a linear range of 0.1 μM to 5 μM and from 5 μM to 150 μM with a low limit of detection (12 nM). Owing to the fouling resistance and anti-interference capabilities of VMSF, the constructed 3D electrochemical sensor can be directly applied for the electrochemical detection of BHA in complex food samples.